The imperial way of life in school education: an investigation into the design and adaptation of the German state of Hesse curricula in the subject of politics/economics - Zimmermann, Tom (Momentum Quarterly, 2023)
School education socialises us from an early age thus shaping our ideas about the world. This paper uses the dualistic conception of different ways of life according to Ulrich Brand and Markus Wissen as the basis for an exemplary analysis of existing curricula in the subject of politics/economics in the German state of Hesse. For this purpose, I describe the current „imperial way of life“ according to Brand and Wissen as a definition of the consequences of our current externalisation society and the „solidary way of life“ as the counter-conception necessary for a transformation. Against the background of this description, I examine sections of recent curricula for the subject politics/ economics in exemplary fashion. In doing so, I find that especially in formal education, an imperial way of life tends to be reproduced and consolidated. However, the comparison of the 2002 curriculum with the 2016 core curriculum also shows that aspects of a „solidary way of life“ are now increasingly being addressed. In order to be able to push this even further, I briefly explain in the conclusion the possibility of strengthening this trend through Education for Sustainable Development.
Keywords: Curriculum analysis, education for sustainable development, imperial way of life, politics/economy, solidary way of life